"Fallen but Charming Creatures": The Demimondaine in Russian Literature and Visual Culture of the 1860s. Issue 1 (3rd January 2019) - LUCEY, COLLEEN
Abstract : This article examines the portrayal of the demimondaine in Russian literature and visual culture of the 1860s. Often referred to as kamelii (camellias) after Alexandre Dumas fils' La Dame Aux Camelias (1848), such "fallen women" entered the cultural imagination through works of art and fiction that associated the demimondaine with pleasure and leisure. Taking the work of Vsevolod Krestovskii (1840–95) as case study, I compare the author's short story "Pogibshee, no miloe sozdanie" ("A Fallen but Charming Creature, " 1861) with a virtually unknown album of salacious lithographs for which Krestovskii provided prurient captions. Titled Pogibshie no milye sozdaniia ( Fallen but Charming Creatures, 1862–63) in reference to his earlier tale, the album glorifies the demimondaine as a new kind of urban woman who possesses sexual and financial agency. Analyzing the depiction of kamelii in these two works–one fiction, the other visual–shows that although they differ in focus, both the story and album commodify the demimondaine for mass circulation.